The influence of providing health education on adolescent knowledge about HIV/AIDS in the Benteng Karang Health Center work area - Helwend, Bertha Ruth; Fajar, Harianti (CV. Paperhome Indonesia, 2025)
Background: Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) remain significant global health problems, especially among adolescents. The low knowledge and awareness of adolescents about HIV/AIDS contributes to the increase in infection rates. Health education plays an important role in improving adolescents' understanding of this disease. This study aims to analyze the effect of health education on increasing adolescent knowledge about HIV/AIDS in the working area of the Benteng Karang Health Center. Methods: This study uses a pre-experimental design with a one-group pretest-posttest approach. A total of 30 teenagers from the Tunas Gospel Message, Sunday School (SM-TPI) of the Benteng Karang Congregation were selected as respondents through a total sampling technique. Health education is provided in the form of counseling, and data is collected using pre-test and post-test questionnaires. Data analysis was carried out with the Wilcoxon test to measure changes in knowledge levels before and after the intervention. Results: Before counseling, 30% of adolescents had good knowledge, 40% enough, and 30% less. After counseling, the number of adolescents with good knowledge increased to 53.3%, 29.2% moderately, and 18.8% less. Statistical analysis showed an increase in the median knowledge score from 6 (IQR 5-7) to 9 (IQR 8-10) with the Wilcoxon test resulting in values of Z = -4.57 and p = 0.000 (p < 0.05), which showed a significant increase in knowledge level. Conclusion: Health education has been proven to be effective in increasing adolescents' knowledge about HIV/AIDS. These results emphasize the importance of continuous education programs to increase adolescents' awareness of HIV/AIDS prevention and control. Therefore, educational interventions through counseling methods need to be applied more widely to maximize their positive impact on society